Classroom Visitation and Workshop Techniques as Predictors of Teachers' Productivity in Secondary Schools in Kwara State (Kwasu International Journal of Educational Management and Leadership, 2026)
The study investigated principals’ classroom visitation and workshop technique as predictors of teachers' productivity in secondary schools in Ilorin South Local Government Area. The study which employed a descriptive survey identified two principals’ supervisory techniques which were classroom visitation, and workshop techniques. Four objectives, two research questions and two null hypotheses were raised for the study. The population consisted of 1,258 principals and teachers in senior secondary schools in Ilorin South Local Government, Kwara State. 330 respondents, which included 24 principals, and 306 teachers were selected using multistage sampling technique. Two set of questionnaires titled “Principal Supervisory Techniques Questionnaire (PSTQ) and Teachers Productivity Questionnaire (TPQ)” were designed for the study. The reliability of the instrument was ascertained using the Cronbach Alpha method to obtain the r-coefficient of 0.83. The research questions were analysed using descriptive statistics of mean and standard deviation. Linear Regression was used to test the null hypotheses of the study at 0.05 level of significance. The findings of the study revealed that principals’ classroom visitation techniques used in public secondary schools involved engagement in collaborative discussions with teachers, visitation to identify professional development needs of teachers, classroom observation on instructional practices, and students’ engagement. The findings also revealed that principals’ supervisory techniques (classroom visitation, workshop and demonstration techniques) significantly influenced teachers’ productivity in public secondary schools. It was concluded therefore that principals’ classroom visitation and workshop techniques can sustain high levels of teacher productivity, ultimately improving the quality of education in public secondary schools. Based on the findings, three recommendations were proposed, among which were that principals should prioritize regular and structured classroom visitations to observe teaching practices, engage in collaborative discussions with teachers, and identify professional development needs of teachers.